(Nie)widzialne seniorki. Wizerunek kobiety starzejącej się w najnowszej literaturze rosyjskiej = (In)visible female seniors. The image of an ageing woman in the latest russian literature - Kalita, Liliana (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the article is the image of ageing women in the latest Russian prose, in works by Nina Katerli, Ludmila Pietruszewska, Wiktoria Tokariewa, Swietłana Wasilenko and Irina Polanskaja. The text concentrates especially on the image of heroines that experience the first stage of the old age, which falls within the period between 50 and 65 years of age.
Keywords: literatura rosyjska; 20 w.; 21 w.; społeczeństwo; kobieta; starzenie się społeczeństwa; Russian literature; ageing societies; woman; Russia; society